2012
DOI: 10.4025/actascieduc.v34i2.16716
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between High School teachers’ wellbeing and teachers’ efficacy

Abstract: ABSTRACT. The purpose of this study was to find out the relationships between high school teachers' wellbeing and their efficacy. The methodology of this study was that of a quantitative research. The population of this study was all high schools' teachers in 9 th to 11 th grades in Zahedan, Iran. Out of 315 samples, the valid sample of this study was 290. The two questionnaires employed here were The Oxford Happiness Questionnaire of the Hills and Argyle (2002) and Teachers' Sense of Efficacy Scale of the Tsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
(8 reference statements)
3
16
0
9
Order By: Relevance
“…As a result of the research, teachers' psychological well-being (X =3.82) is found high. This result matches with the results of the researches by Mehdinezhad (2012); Konu, Viitanen and Lintonen (2010). In his study, Özen (2010) stated that psychological well-being is effective in development of personal responsibility behaviour.…”
Section: Resultssupporting
confidence: 87%
“…As a result of the research, teachers' psychological well-being (X =3.82) is found high. This result matches with the results of the researches by Mehdinezhad (2012); Konu, Viitanen and Lintonen (2010). In his study, Özen (2010) stated that psychological well-being is effective in development of personal responsibility behaviour.…”
Section: Resultssupporting
confidence: 87%
“…A limited number of studies were found pertaining to the effect of teachers' wellbeing on their self-efficacy (e. g., Mehdinezhad, 2012;Vaezi & Fallah, 2011). However, to the knowledge of the researchers, no significant research has been undertaken either abroad or in Pakistan on the effect of the dimensions of wellness (predictor variables) specifically on male and female teachers' self-efficacy as a consequence of a wellbeing course.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…In addition to the quality of their relationships with coworkers and school administrators, job satisfaction and motivational level of teachers are affected by the achievement of their students (Ciftci & Ozcan, 2014). The efficacy of teachers is affected by their happiness level (Mehdinezhad, 2012). Yadav (2012) presents evidence that teachers' effectiveness and their happiness level have a high correlation.…”
Section: English Version Introductionmentioning
confidence: 99%
“…Bununla birlikte, öğretmenlerin iş arkadaşları ve okul yöneticileri ile olan ilişkilerinin kalitesi, iş doyumu ve güdülenme düzeyleri, öğrencilerinin başarılarından etkilenmektedir (Ciftci ve Ozcan, 2014). Öğretmenlerin etkililiği, mutluluk düzeylerinden etkilenmektedir (Mehdinezhad, 2012). Yadav (2012), öğretmenlerin etkililikleri ve mutluluk düzeyleri arasında yüksek düzeyde ilişki olduğuna dair kanıtlar ortaya koymaktadır.…”
Section: Introductionunclassified